2018
DOI: 10.1002/fsn3.889
|View full text |Cite
|
Sign up to set email alerts
|

Walnut oil improves spatial memory in rats and increases the expression of acid‐sensing ion channel genes Asic2a and Asic4

Abstract: Although Walnut oil (WO) has been reported to enhance cognitive function, the underlying molecular mechanisms are not well understood. This study was designed to assess the effects of WO on spatial memory in rats through modulation of the expression of acid‐sensing ion channel genes, Asic2a and Asic4. To investigate the effect of WO on cognitive performance, we supplemented the diet of female rats with WO. The results showed that supplementation with WO at doses of 2.2 and 11 g kg−1 day−1 significantly improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 51 publications
0
8
0
1
Order By: Relevance
“…A recent study by Mejias et al found that IL1b was increased in aged mice and rats (Mejias et al 2018 ; Mawhinney et al 2011 ). Lynch et al, as well as Minogue et al indeed found that EPA reduced hippocampal IL1β expression in rats (Lynch et al 2007 ; Minogue et al 2007 ). Similarly to Moon et al, who reported a reduced IL1β expression and PGE2 levels in BV2 microglia upon EPA treatment, the walnut diet showed similar trends in the liver for both analytes.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A recent study by Mejias et al found that IL1b was increased in aged mice and rats (Mejias et al 2018 ; Mawhinney et al 2011 ). Lynch et al, as well as Minogue et al indeed found that EPA reduced hippocampal IL1β expression in rats (Lynch et al 2007 ; Minogue et al 2007 ). Similarly to Moon et al, who reported a reduced IL1β expression and PGE2 levels in BV2 microglia upon EPA treatment, the walnut diet showed similar trends in the liver for both analytes.…”
Section: Discussionmentioning
confidence: 95%
“…Spatial memory was significantly improved in the Wal and WalEE groups. Wang et al also found that rats administered with 1.1 g/kg, 2.2 g/kg and 11 g/kg walnut oil showed improved cognitive performance in Morris Water Maze (MWM) experiments vaguely based on the concentration used (Wang et al 2018). Other studies in rats and mice also found significant improvements using a 6% walnut-enriched diet in MWM test (Willis et al 2009;Muthaiyah et al 2014) and T-Water maze test (Muthaiyah et al 2014).…”
Section: Cognitive and Motor Functionmentioning
confidence: 94%
“…However, later experiments did not confirm such difference, showing the same performance of control and ASIC1a-null mice [ 136 ]. Another paper connects ASICs with spatial memory, in which authors found that dietary walnut oil improved performance of rats in the Morris water maze [ 137 ]. Also, adding this substance to the hippocampal neurons culture medium leads to an increase in the expression of ASIC2a and ASIC4 genes.…”
Section: Physiological Roles Of Asics In the Brainmentioning
confidence: 99%
“…Numerous studies have reported the antioxidant effects of walnut and confirmed that polyphenols in walnut oil play a role (Jahanban‐Esfahlan et al, 2019; Sánchez‐González et al, 2017). Walnut oil showed anti‐inflammatory (Ganji et al, 2019), antitumor (Batirel et al, 2018), immunomodulatory (Soussi, Gargouri, & El Feki, 2018), neuroprotective (Wang, Yi, et al, 2018), and cardioprotective (Lozano et al, 2013) activities. It is also used to treat diabetes (Sun et al, 2020) and hyperlipidemia (Zibaeenezhad et al, 2003).…”
Section: Introductionmentioning
confidence: 99%